Do College Students Still Need the TOEFL Test as One of Graduation Requirements? - Wahyuni, Linna Endah Nur (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
For the last five years of conducting TOEFL as a graduation requirement, IAI Al Muhammad Cepu only focused on how to succeed in the test. Meanwhile, the students’ perception of the TOEFL test tends to be ignored. Based on the phenomenon explained above, the writer intended to gain the pros and cons of students’ perception on the TOEFL test as one of the graduation requirements, also whether the TOEFL preparation class is needed or not. This study became essential to be conducted since the findings will be beneficial for many universities considering the regulation for conducting TOEFL Test as one of the graduation requirements. The writer used a qualitative method in which questionnaire and interview as the instruments. From 68 participants who filled out the questionnaire and 12 participants involved in the interview; the findings showed that nearly all participants had pros perception on TOEFL as a graduation requirement. Most of the participants considered TOEFL motivated them to learn English better. Besides, few students had cons perception on the TOEFL test. The students encountered some challenges including little knowledge of the material, grammar mastery, and technical errors during the test. Moreover, the finding revealed that most students perceive that an intensive preparation class is strongly needed.